2022
DOI: 10.1027/2151-2604/a000497
|View full text |Cite
|
Sign up to set email alerts
|

A Consequential Partnership

Abstract: Abstract. Many studies have focused on the effects of teachers’ well-being on the development of students, in particular their academic achievement. To date, little is known about the association between teachers’ well-being and students’ well-being. In the present study, we analyzed this relationship and examined the mediating role of teacher support using linked data from 2,686 students and 805 teachers from 48 schools in Germany. Multilevel regression analyses showed a relationship between teachers’ emotion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…Enthusiasm (ENT) is measured using scales derived from Keller et al [94] and Bilz et al [95], evaluating teachers' passion and energy in engaging students. Organization (ORG) is gauged based on Emmer and Sabornie [96] and Hattie [97], focusing on teachers' capability to manage classroom activities and foster a structured learning environment. Passion (PAS), as a key driver of effective teaching, is measured through items reflecting the insights of Day [98] and Palmer [99], highlighting the intensity and dedication of teachers to their profession.…”
Section: Measurement Itemsmentioning
confidence: 99%
“…Enthusiasm (ENT) is measured using scales derived from Keller et al [94] and Bilz et al [95], evaluating teachers' passion and energy in engaging students. Organization (ORG) is gauged based on Emmer and Sabornie [96] and Hattie [97], focusing on teachers' capability to manage classroom activities and foster a structured learning environment. Passion (PAS), as a key driver of effective teaching, is measured through items reflecting the insights of Day [98] and Palmer [99], highlighting the intensity and dedication of teachers to their profession.…”
Section: Measurement Itemsmentioning
confidence: 99%
“…Positive associations between the teacher's well-being and students' academic achievement (Herman et al, 2018) could be explained by the teacher's capacity to adopt more supportive behavior and be successful in their role when they can manage their stress and sustain their personal well-being. Empirically examined positive relations have also been found between teachers' and their students' well-being in such domains as teachers' psychological well-being and students' satisfaction with the school, as well as teachers' emotional exhaustion and students' subjective health complaints (Bilz et al, 2022). Bilz et al conclude that perceived teacher support has a mediating role in the relationship between teacher well-being and student well-being, proposing to proceed with research on what specific teacher behavior supports their students' satisfaction with their school and, ultimately, students' health.…”
Section: Introductionmentioning
confidence: 99%
“…Research has established that the job-related well-being of teachers is an important factor in their professional practice. This relates, in particular, to the social and emotional aspects of their work, often in interaction with others, especially their students and colleagues (Bilz et al. , 2022; McCallum and Price, 2010, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Research has established that the job-related well-being of teachers is an important factor in their professional practice. This relates, in particular, to the social and emotional aspects of their work, often in interaction with others, especially their students and colleagues (Bilz et al, 2022;Price, 2010, 2016). Carroll et al (2021) investigated the downstream effects of teacher well-being and found that changes in well-being affect teachers' instructional quality and their students' well-being.…”
Section: Introductionmentioning
confidence: 99%